2017
DOI: 10.1016/j.jcv.2017.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of an epidemic outbreak of acute hepatitis C in HIV-infected patients by ultra-deep pyrosequencing

Abstract: Word countAbstract: 238 words Main text: 2476 words Highlights-HCV infection has spread among HIV-infected MSM through a local network in Barcelona.-A novel method based on low genetic differentiation is proposed to define transmission groups.-Several potential clusters are identified: 8 for gt1a, 1 for gt1b and 7 for gt4d.-HCV gt4d strains cluster with HIV-infected MSM from other European countries. *Highlights (for review)1 Abstract 1Background: The incidence of acute hepatitis C (AHC) among HIV-infected men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 30 publications
0
14
0
1
Order By: Relevance
“…Several recent studies reported similar results in the MSM population, with an increasing incidence rate in recent years in relation to high-risk sexual practices [ 17 , 18 , 19 , 20 , 21 ] and HCV transmission clusters have even been identified in series of cases of acute hepatitis C [ 22 , 23 ].…”
Section: Epidemiology Of Hcvmentioning
confidence: 55%
“…Several recent studies reported similar results in the MSM population, with an increasing incidence rate in recent years in relation to high-risk sexual practices [ 17 , 18 , 19 , 20 , 21 ] and HCV transmission clusters have even been identified in series of cases of acute hepatitis C [ 22 , 23 ].…”
Section: Epidemiology Of Hcvmentioning
confidence: 55%
“…In this study, we found that HCV molecular phylogenetics identified the transmission of a specific lineage (cluster A) of HCV G4d among men in Quebec; this would otherwise have remained undocumented. The G4d cluster A strains were found to be concentrated in two urban health regions (X and Y) and localized on the same monophyletic lineage as G4d sequences reported in HIV-positive MSM in England, France, Germany and the Netherlands (20, [23][24][25] and later in Spain (30). Although it is likely that this particular G4d cluster A strain was introduced to Canada from Europe, the origin of this strain in Quebec remains unknown.…”
Section: Discussionmentioning
confidence: 66%
“…1,9 Most acute outbreak reports refer to sexual transmission among men who have sex with men or transmission in a healthcare setting. [14][15][16][17][18] Outbreaks of hepatitis C in PWID are difficult to distinguish from background prevalence due to often infrequent testing in this group. In this case, detection of the outbreak followed the identification of four acute or recent cases in a group of young and vulnerable people and provided an opportunity to intervene at an early stage of the event.…”
Section: Discussionmentioning
confidence: 99%
“…Having ever been to prison was reported by 75% of respondents (83% of hepatitis C positive) and 12% reported injecting drugs in prison (30% of hepatitis C positive). Individuals were in prison for a median of four times (range 1-30) and their age at their first prison stay was 18 (range [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Risk Behaviours Analysismentioning
confidence: 99%